2020
DOI: 10.1108/jqme-03-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance strategy selection: a combined goal programming approach and BWM-TOPSIS for paper production industry

Abstract: PurposeCorrect and well-planned maintenance based on modern global methods directly affects efficiency, quality, direct production costs, reliability and profitability. The selection of an optimal policy for maintenance can be a good solution for industrial units. In fact, by managing constraints such as costs, working hours and human workforce causing sudden equipment failure, production and performance can increase.Design/methodology/approachTherefore, in this research a model was presented to select the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…With the progression of time, traditional TOPSIS transformed to fuzzy TOPSIS and IF-TOPSIS. Subsequently, these approaches were applied by several researchers in various fields -Credit risk evaluation (Shen et al, 2018); Site selection of wind power plant (Daneshvar Rouyendegh et al, 2018); Sustainable supplier selection (Memari et al, 2019); Paper process industry (Avakh Darestani et al, 2022); Foundry industry (Panchal et al, 2021). In the proposed model first three steps as followed to compute the ranking in IF-TOPSIS are similar to IF-FMEA.…”
Section: If-topsismentioning
confidence: 99%
“…With the progression of time, traditional TOPSIS transformed to fuzzy TOPSIS and IF-TOPSIS. Subsequently, these approaches were applied by several researchers in various fields -Credit risk evaluation (Shen et al, 2018); Site selection of wind power plant (Daneshvar Rouyendegh et al, 2018); Sustainable supplier selection (Memari et al, 2019); Paper process industry (Avakh Darestani et al, 2022); Foundry industry (Panchal et al, 2021). In the proposed model first three steps as followed to compute the ranking in IF-TOPSIS are similar to IF-FMEA.…”
Section: If-topsismentioning
confidence: 99%
“…For example, Tu et al (2020) have used the fuzzy BWM-TOPSIS method to distinguish the relevance of different indicators of water security levels in various regions of North China. Avakh Darestani et al (2022) incorporated the BWM-TOPSIS approach to determine the best maintenance strategy in the paper production industry. Majumder et al (2022) used the fuzzy BWM-TOPSIS to identify the ideal alternative to enhance the effectiveness of the water treatment plant and found that the fuzzy BWM-TOPSIS approach is superior to fuzzy BWM-AHP and other methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With: D ⊂ R n is a finite or non-finite set and f is a function of R n in R m Among the methods of mathematical programming allowing the treatment of the objective function of Eq. ( 1), let us quote the "Goal Programming -GP," retained in this study and that occupies a place of choice; in particular, to pursue several objectives at the same time (Avakh Darestani et al, 2020;Rifai, 1996).…”
Section: Protection Planmentioning
confidence: 99%